2005
DOI: 10.1029/2004ja010995
|View full text |Cite
|
Sign up to set email alerts
|

Polar study of ionospheric ion outflow versus energy input

Abstract: A statistical study of the ion outflow versus energy input is performed by using multi‐instrument data (TIDE, EFI, MFI, HYDRA) from Polar during its perigee auroral passes in the year 2000. Several important physical quantities connected to the ion outflow have been investigated, including the Poynting flux from the perturbation fields (below 1/6 Hz), the electron density, temperature, and the electron energy flux. The perturbation fields used here to calculate the Poynting flux may be associated with the smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 37 publications
8
62
1
Order By: Relevance
“…These are the nightside regions containing the same in situ processes as the dayside auroral regions shown to contain NEIALs. In situ measurements of upflowing ion beams have been shown to be associated with luminous auroral arcs , but the dominant source of nightside ion outflow from the ionosphere to the magnetosphere has been shown to occur in the polar cap boundary and Alfvénic regions, in both nightside and cusp aurora Lynch et al, 1996;Kintner et al, 1996;Norqvist et al, 1998;André et al, 1998;Knudsen and Wahlund, 1998;Lynch et al, 2002;Strangeway et al, 2005;Zheng et al, 2005). The polar cap boundary and Alfvénic regions are characterized by their soft electron precipitation, with energies of less than 1 keV, typically a few hundred eV (Louarn et al, 1994;Chaston et al, 2003Chaston et al, , 1999Arnoldy et al, 1999;Lynch et al, 2007).…”
Section: In Situmentioning
confidence: 99%
“…These are the nightside regions containing the same in situ processes as the dayside auroral regions shown to contain NEIALs. In situ measurements of upflowing ion beams have been shown to be associated with luminous auroral arcs , but the dominant source of nightside ion outflow from the ionosphere to the magnetosphere has been shown to occur in the polar cap boundary and Alfvénic regions, in both nightside and cusp aurora Lynch et al, 1996;Kintner et al, 1996;Norqvist et al, 1998;André et al, 1998;Knudsen and Wahlund, 1998;Lynch et al, 2002;Strangeway et al, 2005;Zheng et al, 2005). The polar cap boundary and Alfvénic regions are characterized by their soft electron precipitation, with energies of less than 1 keV, typically a few hundred eV (Louarn et al, 1994;Chaston et al, 2003Chaston et al, , 1999Arnoldy et al, 1999;Lynch et al, 2007).…”
Section: In Situmentioning
confidence: 99%
“…There are three main regions of outflow at high latitudes: the auroral oval, the cusp, and the polar cap. The auroral oval and the cusp are regions of intense ion outflow in response to strong energy inputs like Poynting flux, particle precipitation, and the work done by strong field-aligned electric fields accelerating ions upwards (Lockwood et al, 1985;Zheng et al, 2005;Moore and Khazanov, 2010;Nilsson et al, 2012). In the absence of such energy inputs, the main source of energy for ion outflow in the polar cap is solar illumination.…”
Section: Introductionmentioning
confidence: 99%
“…In both of these FAST studies, higher-altitude low-frequency wave heating was identified as the source of escape energization of these upflowing populations. Zheng et al [2005] found in a statistical survey of POLAR satellite data that outflowing ions were correlated with soft electron precipitation and to a slightly lesser degree, downward directed Poynting flux. The former finding is in agreement with Seo et al [1997] who identified the anticorrelation of precipitating electron energy and ion up flux at low DE-2 satellite (850 -950 km) altitudes.…”
Section: Introductionmentioning
confidence: 99%